Diaphysator: An online application for the exhaustive cartography and user-friendly statistical analysis of long bone diaphyses - Santos, Frédéric; Lacoste Jeanson, Alizé (American journal of physical anthropology, 2019)
The cross-sectional geometry (CSG) of long bone diaphyses is used in bioanthropology to evaluate their resistance to biomechanical constraints and to infer life-history-related patterns such as mobility, activity specialization or intensity, sexual dimorphism, body mass and proportions. First limited by technical analytical constraints to the analysis of one or two cross sections per bone, it has evolved into the analysis of cross sections of the full length of the diaphyseal part of long bones. More recently, researchers have developed analytical tools to map the cortical thickness of entire diaphyses to evaluate locomotor signatures. However, none of these analytical tools are easy to use for scientists who are not familiar with computer programming, and some statistical procedures-such as mapping the correlation coefficients of the diaphyseal thickness with various parameters have yet to be made available. Therefore, we developed an automated and open-source application that renders those analyses (both CSG and cortical thickness) in a semiautomated and user friendly manner. This application, called "Diaphysator", is associated with another free software ("Extractor", presented in Dupej et al. (2017). American Journal of Physical Anthropology, 164, 868-876). Diaphysator can be used as an online application (https://diaphysator.shinyapps.io/maps) or as a package for R statistical software. Along with the mean maps of cortical thickness and mean CSG parameter graphs, the users can evaluate the correlations and partial correlations of both CSG parameters at every cross section along the diaphyseal length, and cortical thickness data points of the entire diaphysis, with any factor such as age, sex, stature, and body mass.
Keywords: Software; počítačová rentgenová tomografie; diafýzy; software; Anatomy, Cross-Sectional; Humans; cortical area; free software; anatomie průřezová; Female; antropologie fyzická; lidé; cortical thickness; femur; Femur; internet; ženské pohlaví; Data Interpretation, Statistical; Internet; Male; Tomography, X-Ray Computed; Anthropology, Physical; tibie; morphometric maps; Diaphyses; mužské pohlaví; correlation; Tibia; interpretace statistických dat